A handbook of modern history : world history since 1870 - Gibbons, S. R. (London ; New York : Longman, 1986)
An alphabetically arranged handbook identifying events, features, and individuals of world history since 1870, from the Abdication Crisis to the Zulu War.
Includes index.
Keywords: 1800-1999; History, Modern -- 19th century; History, Modern -- 20th century; History, Modern -- 19th century; History, Modern -- 20th century; History, Modern; World, 1870-1984